Factors affecting non-starch polysaccharide digestibility in poultry - Williams P.E.V.; Geraert P.A.; Uzu G.; Annison G. (Feed manufacturing in Southern Europe: New challenges, 1997)
Factors affecting NSP digestibility on poultry diets are reviewed. The variation of plant NSP type and its content are followed by consideration of the effects of NSP on digestibility and overall nutrient digestion. Finally, effects of supplementation with exogenous NSP enzymes are shown in relation to diet composition plus effects of feed processing and animal physiology.
South European Feed Manufacturers Conference, 1996/05/09-11, Reus (Spain)